Nitrogen and Iron Sulfate Affect Microdochium Patch Severity and Turf Quality on Annual Bluegrass Putting Greens. (16th August 2017) - Mattox, Clint M.; Kowalewski, Alec R.; McDonald, Brian W.; Lambrinos, John G.; Daviscourt, Brian L.; Pscheidt, Jay W.
Abstract : Microdochium patch is an important turfgrass disease in cool‐humid regions and is caused by the pathogen Microdochium nivale (Fries) Samuels & Hallett. Control of the pathogen is necessary to provide acceptable putting‐green‐quality turf, and fungicide applications are the predominant method of control. Increasing pesticide restrictions have generated interest in alternative management techniques of Microdochium patch. This research evaluated the effects of three nitrogen and five iron sulfate rates on Microdochium patch development on a trafficked, sand‐based, annual bluegrass ( Poa annua L.) putting green in Corvallis, OR for over 2 yr in the absence of fungicides. Data included turf quality, area under disease progress curve, and soil test results of saturated paste extract pH, cation extractable sulfate, and DTPA‐sorbitol extractable iron. This research provided evidence that low rates of urea (4.88 kg N ha −1 ) applied every 2 wk did not lead to an increase in Microdochium patch severity and that iron sulfate applications decreased Microdochium patch on annual bluegrass putting greens. Despite the disease suppression observed, no treatment received a turf‐quality rating considered acceptable. Low turf‐quality ratings where disease development was low were attributed to turfgrass thinning or blackening of the shoots resulting from iron sulfate applications. Soil tests provided evidence that the highest iron sulfate level used in this study (97.65 kg ha −1 ) applied every 2 wk would likely lead to a lower soil pH and an increase in soil sulfate levels.